Analisa Desain Apartemen untuk Kaum Milenial di Area Transit Oriented Development (TOD) di Indonesia : (Studi Kasus: Rusun Pondok Cina) - Nurlatifah Fajriaty Ronyta (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2023)
Indonesia is expected to enter the Demographic Bonus era, a condition where the population of productive age is greater than that of non-productive age. This dominant generation of productive age can also be called the Millennial Generation. According to data held by BPS regarding the increase in Indonesia's population in 2015, the percentage of the working age population was around 70%. The Demographic Bonus has the potential to spur Indonesia's economic growth. However, this condition has requirements, namely the need to provide housing facilities that can accommodate the percentage of the working age population in the range of 70%. The Demographic Bonus has the potential to spur Indonesia's economic growth so that it is hoped that it can improve the welfare of the Indonesian people. However, this condition has requirements, namely the need to provide housing facilities that can accommodate these millennials. Moreover, the current urbanization trend is encouraging the millennial generation to work in big cities in Indonesia. Providing housing facilities in areas supported by adequate transportation facilities or transit/TOD-based housing development can increase the work productivity of millennials. However, the challenges faced in housing services in TOD areas are land issues and ownership status owned by private parties because strategic locations have higher value from an economic perspective. If this happens, then residences in TOD areas will become typical residences intended for people with high incomes. On the other hand, not all millennials are high-income people. In terms of age, most millennials are still in the middle and lower category because they are still at the stage of starting their careers, so providing housing facilities for millennials does not only pay attention to location, but also to economic aspects. In this article, we discuss affordable housing in TOD areas as fulfilling housing needs for millennials along with concepts from an architectural perspective that have been implemented in Indonesia and in several countries in the world as a comparison so that they can be input for special development of affordable housing in TOD areas for millennials in Indonesia.